Efficacy of a remote control closure of cod-end used in a bottom trawl experience - Francesc Sardà; Joan B. Company; Miguel A. Estevez (Scientia Marina, 2002)
A total of 26 effective trawl hauls using a remotely operated trawl cod-end closure system were carried out to determine whether samples collected in a rear section of the cod-end and in a front section of the cod-end were homogeneous, and can be used as reliable replicates for community sampling and resource assessment. Comparative analyses of these sample hauls and 25 other hauls that did not use the cod-end closure system were also performed. The results indicate certain technical difficulties in the practical operation of the system and that samples were not homogeneous either between the cod-end sections in the same haul or between hauls. The causes of the sample variability in catches from trawl surveys are discussed.